Co-occurrence of insufficient physical activity, smoking, inadequate diet, and alcohol consumption in university students from Minas Gerais, Brazil - Farias, Gildeene Silva; Andaki, Alynne Christian Ribeiro; Fonseca, Silvio Aparecido; Franco, Dayana Chaves; Sousa, Thiago Ferreira de (Revista Sustinere, 2023)
The aim of this study was to estimate the prevalence and factors associated with the co-occurrence of insufficient physical activities, smoking, consumption of alcoholic beverages, and inappropriate eating habits in university. This is a cross-sectional study with a representative sample of students from the Federal University of Triângulo Mineiro, MG, Brazil. The information was obtained through a questionnaire and the risk criteria adopted were irregular consumption of fruits and vegetables, insufficient physical activity, smoking, and excessive consumption of alcoholic beverages. The independent variables were sex, age group, marital status, area of study and time of study. The outcomes were the co-occurrence of two and three/four risk factors. The association was measured using Odds Ratio (OR) and a multinominal logistic regression with a significance level of 5%. 1.110 university students participated. The prevalence of two and three/four risk factors was of 35.3% and 15.4%, respectively. College students with a partner were associated with lower chances for two risk factors (OR: 0.45; 95% CI: 0.21–0.98), and there was an association between three or four factors of behavioral risk with university students belonging to areas not related to health (OR: 1.90; 95% CI: 1.26–2.86). It was concluded that the prevalence of occurrence of two risk factors or more was high and that single students and those in fields unrelated to health were associated with the risk factors.